History of women's costume - Sichel, Marion (New York : Chelsea, 1984)
Traces the history of women's clothing from its ancient Greek and Roman origins through the 1930s.
Includes bibliographical references and index.
10-A.
Keywords: Women's clothing -- History; Women -- Costume -- History; Women's clothing -- History; Women -- Costume -- History